The Role of a Sensory Diet in Improving the Quality of Psychosocial Functioning of Students in Inclusive Education - Magdalena Wójcik (Jan Dlugosz University, 2023)
Effective sensory processing is necessary for physiological regulation, the generation of appropriate behavioural responses and the development of academic skills. The physical environment in the classroom and at school can impact a child's ability to become engaged in education. By creating proper sensory diets and a sensory-friendly classroom, teachers can help children achieve an optimal level of arousal and become successful students. That is why paying attention to the possibilities of creating a sensory-friendly environment is so essential as providing the appropriate amount of sensory stimuli tailored to students' needs and capabilities. An in-depth literature review has been carried out to justify the role of a sensory diet and a sensory-friendly classroom. Analysing the theoretical and scientific context justifies the development of sensory programs in inclusive education. It shows the possibilities for both using and adapting them to the needs of students.